Social-Harmony within Aceh Society: An Analysis towards Religious Tolerance of Muslim and Non-Muslim Communities in Banda Aceh - Inayatillah Inayatillah (Millati: Journal of Islamic Studies and Humanities, 2021)
This paper examines how social harmonization can be realized in Aceh since the independence of the Republic of Indonesia until now. The people of Aceh are a pluralistic society, although the majority are Muslim, the problem of conflict between religious communities is rare. Even after the province implemented Islamic Sharia, inter-religious harmony remained closely intertwined. Therefore, there is a need for a study that looks at the social harmonization aspects of religious tolerance, especially in daily behavior terms of Muslim and non-Muslim communities in Banda Aceh city. This paper shows that religious tolerance in Aceh is running as it has in other provinces even though the province has been designated as an area that implements Islamic Shari'a. This can be seen from the interactions that exist between Muslims and non-Muslims in various community activities. Based on the author's observations and experiences, it shows that the religious harmony of the Acehnese people is very deep. Some of the authors' findings in looking at the depth of tolerance include that non-Muslims can live side by side and gain freedom in carrying out their religious life. In addition, between them also established business interactions, cooperation, and involvement in socio-political life. In addition, the active role of non-Muslim communities through the association has strengthened this harmony. Non-Muslims in Aceh have developed mutual respect and compassion through social activities.